The basis for camptothecin enhancement of DNA breakage by eukaryotic topoisomerase I. - Porter, S E (1989)
The eukaryotic topoisomerase I (topo I) is the target of the cytotoxic alkaloid camptothecin (CTT). In vitro, CTT enhances the breakage of DNA by topo I when the reaction is stopped with detergent. Although breakage at some sites is enhanced to a great extent while breakage at others is enhanced only minimally, CTT does not significantly change the breakage specificity of topo I in vitro. It has been suggested that CTT acts by slowing the reclosure step of the nicking-closing reaction. To test this hypothesis, we have measured the rate of reclosure for different break sites in the presence of CTT after adding 0.5 M NaCl to a standard low salt reaction. In support of the hypothesis, we find that topo I-mediated DNA breakage is enhanced the greatest at those sites where closure of the break is the slowest. These results suggest a mechanism for the toxicity of CTT in vivo.